Hubungan Riwayat Merokok Dengan Stadium Ca Paru - Herlina - -; Siti Rahmalia HD; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this study was to determine the cigarette history with lung cancer stadium. The research method is descriptive correlation. The study was conducted in Arifin Achmad Pekanbaru hospital with a sample of 33 patient. The sampling method is purposive sampling. Data collection tool in this study is a questionnaire with 4 question and observation sheet result from read CT Scan. An analysis is univariat and bivariate analysis using chi-square test. The result showed that there is a relationship between cigarette history with lung cancer stadium with p value ( 0,035) < α (0,05) in Arifin Achmad Pekanbaru hospital in Arifin Achmad Pekanbaru hospital. This study is suggested to the health worker to give education for society about cigarette danger for the happening of cancer lung and result of this research also expected upon which the reference program of study of science and also relevant institute. Keywords : Lung Ca, smoking history, stage